Benzodiazepines and z-drugs - between treatment effectiveness and the risk of addiction - Cabaj, Justyna; Bargieł, Julia; Soroka, Ewelina (Journal of Education, Health and Sport, 2023)
Benzodiazepines (BZDs) and Z-drugs are commonly prescribed medications for anxiety and sleep disorders. This review examines their efficacy, associated risks, and alternative treatment options. BZDs enhance the activity of gamma-aminobutyric acid (GABA), reducing anxiety, while Z-drugs selectively target GABA-A receptors' alpha-1 subunits for sedative effects. Despite their effectiveness, both drug classes carry the risk of addiction, physical and psychological dependence, and withdrawal symptoms. Side effects, such as drowsiness, dizziness, and cognitive impairment, are also associated with their use. Recent studies indicate that chronic use of BZDs and Z-drugs may lead to cognitive impairment and an increased risk of dementia in older adults. Furthermore, individual factors, dosage, duration of use, and drug interactions can affect their efficacy. Prescribing trends show a decline in benzodiazepine prescriptions and an increase in Z-drug use due to perceived safety advantages. However, evidence suggests that Z-drugs carry similar risks of adverse effects and addiction potential as benzodiazepines. Healthcare professionals should carefully assess patients before prescribing these drugs and monitor their use to prevent dependence and addiction. Brief interventions, patient education, drug withdrawal support, and cognitive behavioral therapy have shown effectiveness in reducing long-term benzodiazepine and Z-drug use. Alternative treatments, including cognitive behavioral therapy and relaxation techniques, should be considered, particularly for patients with a history of addiction or those at high risk of addiction. In conclusion, the risk of addiction, withdrawal symptoms, and adverse effects associated with benzodiazepines and Z-drugs necessitates cautious prescribing and the exploration of alternative treatment options.<span class="EOP SCXW220928152 BCX8" data-ccp-props="{"134233117":false,"134233118":false,"134245417":true,"134245418":false,"134245529":false,"201341983":0,"335551550":6,"335551620":6,"335559685":0,"335559731":0,"335559737":0,"335559740":259}">